Thyroidectomy in octogenarians is not associated with poorer postoperative outcomes. Issue 8 (4th March 2019) - Wong, Eugene H.; Smith, Murray; Fish, Brian; Jani, Piyush; Palme, Carsten E.; Smith, Mark C.; Riffat, Faruque
Abstract: Background: The elderly represents one of the most rapidly growing subsets of the population. This population experiences a higher incidence of thyroid pathology. However, there are concerns that the elderly also experiences increased perioperative complications and are poor candidates for thyroidectomy. Methods: Patients who underwent thyroidectomy over the age of 80 years at three tertiary head and neck units were included. Data regarding age, sex, presenting symptoms, comorbidities, preoperative investigations, type of surgery, postoperative complications, and final thyroid pathology were retrieved from hospital records. Results: Of a total of 39 patients (69% women, mean age 83.1), the majority (40.1%) presented with a combination of symptoms: shortness of breath, feeling of pressure in the neck, dysphagia, or tiredness. Two (5.1%) were asymptomatic. Low rates of postoperative complications were encountered and were minor ( n = 5). No intensive care unit admissions or mortality was experienced. Conclusion: Thyroid surgery in octogenarians carries an acceptable complication profile.